Does Sestrin-1 Mitigate Cardiovascular Risks in Radiographic Axial Spondyloarthritis? - Selman Parlak; Ahmet Taha Sahin; Ahmet Lütfü Sertdemir; Adem Küçük; Abdullah İçli (Archives of Rheumatology, 2025)
Background/Aims: Radiographic axial spondyloarthritis (r-axSpA) is a chronic inflammatory arthritis associated with increased cardiovascular (CV) risk due to persistent inflammation. Sestrin-1, an antioxidant and anti-inflammatory protein, has been implicated in CV protection. This study investigated relationships between Sestrin-1 levels, CV markers, and echocardiographic findings in r-axSpA patients. Materials and Methods: Controlled study of 48 r-axSpA patients (modified New York criteria) and 48 age- and sex-matched healthy controls. Collected demographic, biochemical, and echocardiographic data. Measured Sestrin-1 by ELISA; assessed carotid intima-media thickness via ultrasound. Statistical analyses evaluated group differences and correlations between Sestrin-1 and inflammatory/CV parameters. Results: r-axSpA patients had significantly lower Sestrin-1 levels than controls (P = .003). Sestrin-1 negatively correlated with CRP (r = –0.42) and ESR (r = –0.38). Echocardiography showed increased CIMT (P < .001), reduced RVSM, and lower TAPSE in r-axSpA patients. No correlation between Sestrin-1 and ASDAS-CRP. Conclusion: r-axSpA patients exhibit reduced Sestrin-1 and subclinical CV changes, suggesting Sestrin-1 may contribute to CV risk in r-axSpA. Further research is needed on Sestrin-1 as a biomarker for CV complications.